CASTRATION OF SEX OFFENDERS: INDONESIAN CRIMINAL LAW REFORM - Widiyaningrum, Irene; Akub, M. Syukri; Razak, Abdul; Riza, Marwati (Hasanuddin Law Review, 2019)
The rise of cases of sexual violence today makes people become restless. This research is a normative legal research, where in this study the author analyzes various laws and regulations relating to sanctions for chemical castration in the perspective of criminal law. This study also uses various comparisons of theories to answer existing problems relating to criminal law policy in the case of applying chemical castration sanctions. The results show that The increasingly widespread cases of sexual crimes against children that can have a major impact on the child's psychic development. It deserves to be given a severe punishment and appropriate to the perpetrator. The imprisonment sanction that is deemed to be irrelevant and has no deterrent effect can be answered by the punishment of the last choice of child sex offender. Thus, the enforcement of the criminal law of nuisance is reasonable in the technical context of the sentence after a permanent legal court ruling stating the punishment of the left. It aims to create a comfortable environment where children grow and develop and guarantee the future of Indonesian children.